Pulp Vitality and Longevity of Adhesive Restorations Are Not Affected by Selective Carious Removal: A Multicenter Clinical Trial - Olegário, Isabel (My University, 2021)
The aim of this multicenter randomized clinical trial was to evaluate the pulp vitality and survival rate of adhesive restorations performed on posterior deciduous teeth after non-selective (NSCR) or selective (SCR) carious tissue removal over 33 months. One hundred and seven children (average age 4-8 years, SD 1.4) with at least two active moderate cavitated lesions in dentin were included. Teeth were randomized and submitted to NSCR or SCR before composite resin restoration. Restorations were clinically and radiographically assessed at baseline, 6, 12, 18, 24, and 33 months by a blinded, trained, and calibrated operator in each center. The characteristics of the restorations were recorded according to FDI criteria and were considered as restorative failures when scores 4 or 5 were presented. Pulp vitality was measured by clinical and radiographic examinations, and those teeth that presented any signs or symptoms of irreversible pulpitis or pulp necrosis were considered as failure. Data were analyzed by a Cox regression model with shared frailty, considering two outcomes: pulp and restorative. A total of 278 restorations (137 after NSCR and 141 after SCR) were performed at baseline in four different centers and there was no loss in the follow-up period. Survival rate was 97.1 and 87.1% for pulp and for restorative outcome, respectively. The overall annual failure rate was 7%. There were no differences in the failure risk according to the treatment group, center, and all the clinical and demographic variables, regardless of outcome. Composite restorations of active moderate deep carious lesions performed on posterior primary teeth show satisfactory survival for restorative and pulp outcome after a 33-month follow-up, regardless of the technique executed for carious tissue removal.
Keywords: Survival analysis; Selective caries removal; Pulp vitality; Multicenter study; Composite resin; Dental restoration